2008
DOI: 10.1200/jco.2008.17.0829
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Centrally Reviewed Ki-67 Labeling Index in Postmenopausal Women With Endocrine-Responsive Breast Cancer: Results From Breast International Group Trial 1-98 Comparing Adjuvant Tamoxifen With Letrozole

Abstract: A B S T R A C T PurposeTo evaluate the prognostic and predictive value of Ki-67 labeling index (LI) in a trial comparing letrozole (Let) with tamoxifen (Tam) as adjuvant therapy in postmenopausal women with early breast cancer. Patients and MethodsBreast International Group (BIG) trial 1-98 randomly assigned 8,010 patients to four treatment arms comparing Let and Tam with sequences of each agent. Of 4,922 patients randomly assigned to receive 5 years of monotherapy with either agent, 2,685 had primary tumor ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
212
3
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 305 publications
(233 citation statements)
references
References 30 publications
(10 reference statements)
9
212
3
9
Order By: Relevance
“…It was also decided not to use the best, but most likely overfitted, cut-off for Ki-67 but the one calculated from 2685 patients by Viale et al (2008) 11% . The same one was used for UBE2C.…”
Section: Discussionmentioning
confidence: 99%
“…It was also decided not to use the best, but most likely overfitted, cut-off for Ki-67 but the one calculated from 2685 patients by Viale et al (2008) 11% . The same one was used for UBE2C.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear positivity of Ki67 protein is an indication of cell proliferation [6,7] and it has long been reported as a prognostic marker in breast cancer (BC) [8][9][10][11]. There is evidence that tumours with higher expression levels of Ki67 respond better to adjuvant chemotherapy than those tumour having low levels of Ki67 [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the connection with prognosis have been particularly numerous 8,9 , and a near-consensus on this has been reached. The Ki-67 LI was also signi cantly correlated with relapse and prognosis in the present study.…”
Section: Characteristics Of Ki-67mentioning
confidence: 99%
“…Jones et al 24 reported that 400 magnification in 10 elds, counting at least 1000 tumor cells, is essential. However, this method is complex and time-consuming in actual clinical practice, so some facilities use automated measurements assisted by analysis software 8 , and this technique is also reported to be useful for needle biopsy tissue 25 . However, this automated technique tends to count some nontumor cells, such as lymphocytes, thus affecting its accuracy.…”
Section: Determination Of the Ki-67 Labeling Indexmentioning
confidence: 99%
See 1 more Smart Citation